Progress in yield components and yield potential in bread wheat and durum wheat genotypes - Cseuz L.; Kertesz C.; Fonad P.; Kovacs I.; Ovari J.; Matuz J.; Kertesz Z. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
During the 45 years of wheat selection in the 80 year-old Cereal Research Non-profit Co. (CRNC) the bread and durum wheat varieties' grain yields increased significantly. The demands (high grain yield, bread and pasta making quality, higher agronomical claims, tolerance for biotic and abiotic stresses, etc.) marked new priorities for breeding as both the economical and ecological environment changed. In this work the structure and most important components of genetical advance were studied and the answers were tried to find, that as the grain yields increased significantly, how the main yield components changed, and the changes of which characters affected significantly the tolerance to stresses, grain yield, biological yield capacity, and harvest index (HI).
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)